Ocular Manifestations of Human Immunodeficiency Virus – A Review - Sanjay Teotia; Anubha Rathi; Brijesh Takkar; Shorya Vardhan Azad; Deepankur Mahajan; Manzoor Mehdi (Delhi Journal of Ophthalmology)
In spite of the widespread use of highly active antiretroviral therapy (HAART) in the industrialized world, ocular manifestations of Human Immunodeficiency Virus (HIV) at some point affect 50–75% of infected persons worldwide. The spectrum of such manifestations includes infectious, vascular, neoplastic and inflammatory disorders directly or indirectly related to HIV or its treatment. For simplicity, they may be divided into Anterior, Extra ocular, Neuro ophthalmic and Posterior segment manifestation. Screening, prophylaxis, prompt diagnosis, treatment and maintenance is the key.